PERAN KEUNGGULAN BERSAING DALAM MEMEDIASI PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN - Dewi, Ni Made Putri; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 6 No 9 (2017), 2017)
This study was conducted with the aim of explaining the effect of market orientation on competitive advantage, competitive advantage on marketing performance, market orientation to marketing performance and competitive advantage in mediating the influence of market orietation on marketing performance. This research was conducted on the owner or manager of laundry SME in Kecamatan Kuta Selatan. The sample size used in this study was 108 respondents. Determination of sample using technique of NonProbability Sampling with Purposive Sampling. The analytical technique used in this research is Path Analysis and Sobel Test. Based on the results of the data analysis, the overall hypothesis is accepted that market orientation has a positive and significant impact on competitive advantage, competitive advantage has a positive and significant effect on marketing performance, market orientation has positive influence and significant influence on marketing performance, and competitive advantage can positively mediate the effect of market orientation On Marketing performance at SME laundry in Kecamatan Kuta Selatan.